2010
DOI: 10.1261/rna.2384610
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of translational regulation by miR-2 from sites in the 5′ untranslated region or the open reading frame

Abstract: MicroRNAs (miRs) commonly regulate translation from target mRNA 39 untranslated regions (UTRs). While effective miR-binding sites have also been identified in 59 untranslated regions (UTRs) or open reading frames (ORFs), the mechanism(s) of miR-mediated regulation from these sites has not been defined. Here, we systematically investigate how the position of miR-binding sites influences translational regulation and characterize their mechanistic basis. We show that specific translational regulation is elicited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 35 publications
(60 reference statements)
1
99
0
Order By: Relevance
“…This complex binds to the target sequence that is more commonly located within the 3Ј untranslated region (UTR) of the mRNA (10 ). Functional miRNA target sequences in 5Ј UTR and in the open reading frame have also been reported (13 ). The seed region of the miRNA (the first 2-8 nt) is especially important for miRNA target recognition.…”
Section: Function Of Mirnas Mirna Transportation and Signaling Betwmentioning
confidence: 99%
“…This complex binds to the target sequence that is more commonly located within the 3Ј untranslated region (UTR) of the mRNA (10 ). Functional miRNA target sequences in 5Ј UTR and in the open reading frame have also been reported (13 ). The seed region of the miRNA (the first 2-8 nt) is especially important for miRNA target recognition.…”
Section: Function Of Mirnas Mirna Transportation and Signaling Betwmentioning
confidence: 99%
“…Moreover, even though it is known that microRNAs mainly recognize complementary sequences in the 3' untraslated regions (UTRs) of their target mRNAs, more recent studies have reported that they can also bind to the 5'UTR or the ORF [5][6][7][8] and, even more surprisingly, they can upregulate translation upon growth arrest conditions [9] .…”
Section: Mirnas Biogenesis and Mechanism Of Actionmentioning
confidence: 99%
“…7 The mature miRNA is retained in RISC (RNA-induced silencing complex) 8 and it is currently understood that microRNAs mainly bind to the 3' untranslated region (UTR) of their target mRNAs. However, recent studies have reported that microRNAs do not only bind to 3'UTR but also to 5'UTR 9,10 or open reading frame (ORF) 11,12 of the target mRNA. By binding to the 3'UTRs, 5'UTR or ORF of target mRNAs, microRNAs regulate the translation of proteins from mRNA or degrade the mRNA itself.…”
Section: What Is Microrna?mentioning
confidence: 99%